Comparison of Alternative Splicing Junction Detection Tools Using RNASeq Data - Ding, Lizhong; Rath, Ethan; Bai, Yongsheng (Current Genomics, 2017)
Background: Alternative splicing (AS) is a posttranscriptional process that produces different transcripts from the same gene and is important to produce diverse protein products in response to environmental stimuli. AS occurs at specific sites on the mRNA sequence, some of which have been defined. Multiple bioinformatics tools have been developed to detect AS from experimental data. Objectives: The goal of this review is to help researchers use specific tools to aid their research and to develop new AS detection tools based on these previously established tools. Method: We selected 15 AS detection tools that were recently published; we classified and delineated them on several aspects. Also, a performance comparison of these tools with the same starting input was conducted. Result: We reviewed the following categorized features of the tools: Publication information, working principles, generic and distinct workflows, running platform, input data requirement, sequencing depth dependency, reads mapped to multiple locations, isoform annotation basis, precise detected AS types, and performance benchmarks. Conclusion: Through comparisons of these tools, we provide a panorama of the advantages and shortcomings of each tool and their scopes of application.
Keywords: Spliceosome